2015
DOI: 10.1017/s1047951115002334
|View full text |Cite
|
Sign up to set email alerts
|

Common pulmonary vein atresia: report of three cases and review of the literature

Abstract: Common pulmonary vein atresia is a rare and usually fatal congenital anomaly, in which the pulmonary veins come together to form a confluence that does not connect to the left atrium. We report our experience with three cases of common pulmonary vein atresia and review the literature on this anomaly. The diagnosis of common pulmonary vein atresia must be entertained in any newborn that presents with cyanosis, refractory acidosis, and decreased systemic perfusion within the first 48 hours of life. Echocardiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…This discrepancy can be deemed as one of the distinguishing points between the two. 18 However, our results showed no significant difference in the incidence of complex cardiac malformations and AS between the CPVA and TAPVC groups. Therefore, the characteristics of coexisting malformations in TAPVR and CPVA cases may provide little help in the diagnosis or differential diagnosis of these conditions.…”
Section: Re Sultscontrasting
confidence: 62%
See 4 more Smart Citations
“…This discrepancy can be deemed as one of the distinguishing points between the two. 18 However, our results showed no significant difference in the incidence of complex cardiac malformations and AS between the CPVA and TAPVC groups. Therefore, the characteristics of coexisting malformations in TAPVR and CPVA cases may provide little help in the diagnosis or differential diagnosis of these conditions.…”
Section: Re Sultscontrasting
confidence: 62%
“…It is reported that TAPVC is liable to be accompanied by complicated heart malformations or AS, while CPVA seldom coexists with other complex malformations. This discrepancy can be deemed as one of the distinguishing points between the two . However, our results showed no significant difference in the incidence of complex cardiac malformations and AS between the CPVA and TAPVC groups.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations